Torture survivors who engage in advocacy in the U.S.: Review, characteristics and policy implications - Bazaz, Nouf; O'Connor, Seini; Barron, Andrea; Byimana, Léonce; Isley, Jennifer (Torture Journal, 2023)
Introduction: Despite facing many challenges, some survivors of torture seeking asylum in the U.S. have courageously engaged in advocacy efforts to bring attention to human rights issues relevant to their own personal experiences. This study sought to add to our understanding of the characteristics of survivors who engage in advocacy in comparison with those who do not. Method: We analyzed demographic, social, and psychological quantitative data collected from survivors (n=730) connected to a support agency that regularly facilitates advocacy events using between-groups t-tests and regression analyses. Based on theory, clinical insights, and past research around survivor advocacy we predicted that participation in advocacy would be associated with and predicted by factors indicating lower levels of trauma-related symptoms and higher social power and stability. Results: We found no significant difference in clinical symptoms or most demographic or social characteristics between advocacy participants (n=75) and non-participants. However, advocacy participants had spent significantly more time in the U.S. and were less likely to have had employment authorization at time of service intake, and were more likely to be male, compared to non-participants. Without controlling for other demographic factors, higher spirituality and not having been detained at entry to the USA also predicted advocacy participation. Discussion: Our findings suggest that, despite some patterns of difference indicating greater stability and access to power (e.g., being male, having more time in the U.S., more daytime availability, a strong sense of spirituality, and less experience of detention in the U.S.), survivor-advocates are diverse and not consistently differentiated from non-advocates by specific characteristics. Thus, we find no evidence to support using psychological or demographic indicators as a “screening” criterion for selecting advocacy candidates. We contend that it is important to adopt a gender-inclusive approach in providing wider opportunities that help more survivors overcome potential (racial, socio-economic, mental health, etc.) barriers to engagement, and to pay close attention to who is being left out of advocacy opportunities.